2021
DOI: 10.1007/s40279-021-01509-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil for Healthy Aging: Potential Application to Master Athletes

Abstract: Master athletes perform high volumes of exercise training yet display lower levels of physical functioning and exercise performance when compared with younger athletes. Several reports in the clinical literature show that long chain n-3 polyunsaturated fatty acid (LC n-3 PUFA) ingestion promotes skeletal muscle anabolism and strength in untrained older persons. There is also evidence that LC n-3 PUFA ingestion improves indices of muscle recovery following damaging exercise in younger persons. These findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
(177 reference statements)
0
1
0
Order By: Relevance
“…Preliminary studies showed that taking 6 g of fish oil can optimize muscle soreness recovery after heavy exercise (VanDusseldorp et al, 2020). while a daily dose of 250-500 mg/day is recommended (Murphy & McGlory, 2021). However, a higher dose of 8 g did not appear to improve muscle recovery following eccentric resistance exercise (Visconti et al, 2021).…”
Section: Omega-3mentioning
confidence: 99%
“…Preliminary studies showed that taking 6 g of fish oil can optimize muscle soreness recovery after heavy exercise (VanDusseldorp et al, 2020). while a daily dose of 250-500 mg/day is recommended (Murphy & McGlory, 2021). However, a higher dose of 8 g did not appear to improve muscle recovery following eccentric resistance exercise (Visconti et al, 2021).…”
Section: Omega-3mentioning
confidence: 99%